Literature Review Peran Perawat Dalam Edukasi Dan Skrining Kanker Serviks Di Indonesia - Jamila Rambe (STIKES Columbia Asia Medan, 2025)
Cervical cancer remains a significant public health concern for women in Indonesia, especially due to low awareness and limited early detection practices. Nurses play a strategic role in cervical cancer prevention efforts, particularly in providing health education and implementing early screening methods such as the Visual Inspection with Acetic Acid (VIA) test. This literature review aims to examine the involvement of nurses in cervical cancer education and screening across various regions in Indonesia from 2020 to 2025. A total of 18 studies were selected through the PRISMA method and analyzed thematically. The findings indicate that nurses serve not only as health educators but also as frontline practitioners in community-based screening initiatives. Despite their critical roles, nurses face challenges such as lack of training, policy support, and community stigma. This review underscores the need for strengthening the nursing capacity and policy support to optimize their contribution to cervical cancer elimination. The results also provide evidence-based insights for developing future nursing interventions and public health strategies targeting cervical cancer in Indonesia.